Calixarene-supported Pd–NHC complexes as efficient catalysts for scalable Suzuki–Miyaura cross-couplings. Issue 8 (10th July 2020) - Labattut, Axel; Abi Fayssal, Sandra; Buendia, Julien; Abdellah, Ibrahim; Huc, Vincent; Martini, Cyril; Schulz, Emmanuelle
Abstract : Calixarene-supported PEPPSI-catalysts deliver high yielding and almost Pd trace-free Suzuki–Miyaura coupling products. Abstract : Benzyloxycalix[8]arene is reported as a suitable macrocyclic support for Pd–NHC complexes, which catalyses C–C cross-coupling reactions with high efficiency. Resulting PEPPSI-derived complexes, issued from a scalable synthetic procedure avoiding any tedious purification, are indeed used as heterogeneous catalysts in ethanol to promote the Suzuki–Miyaura coupling between various aryl halides and arylboronic acids (or esters). Optimisation of the reaction conditions allowed the use of only a slight excess of base (K3 PO4, 1.2 equivalents) and boronic acid (1.1 equivalents), and these conditions were also successfully applied to a large scale benchmark reaction (1 mole of substrate) using a low palladium loading (0.001 mol%). Furthermore, target products were easily isolated after simple filtration procedures with low residual Pd traces (down to 3 ppm) thanks to the insoluble nature of the macrocyclic catalyst in ethanol, thus proving the usefulness of this support to promote coupling reactions relevant to the fine chemical industry.